‘Urf and Its Role in The Development of Fiqh: Comparative Study of Famliy Law Between Egypt and Indonesia - Fauzi, Fauzi (El-Usrah: Jurnal Hukum Keluarga, 2024)
This research discusses the dynamics of changes in Islamic family law which is strongly influenced by ‘urf as a dynamic and elastic enrichment. The research question is how is the absorption of ‘urf in Egypt and Indonesia in fiqh, what are the rules for its application and contextualization in the development of Fiqh in Indonesia. Methodologically, this type of research is qualitative with documentation, interviews and observation as technical data collection. The data will be analyzed using the ushul fiqh and Sociological approaches. The results of the research are first, the absorption of ‘urf in Egypt and Indonesia is very strong, especially in the field of Islamic Family Law. In determining the dowry, each region has different customs and considerations, both in Indonesia and Egypt. The difference is in terms of joint assets, the wife in Egyptian 'urf is guaranteed to have assets from three sources; grants, gifts from parents and husbands. Meanwhile in Indonesia, joint assets are considered based on their contribution to the family business after marriage, which varies greatly according to prevailing customs. This difference is considered absorbing 'urf in Fiqh as one of the interpreters of nass are in the form of; ‘urf is dependent, dynamic, accommodates values and norms, contributes to the development of Fiqh and fulfills the elements of maqasid sharia. As a finding, in the Contextualization in the Development of Fiqh, ‘urfcontributes to tajdid (renewal) which places more emphasis on mutaghayyirat of the family law. There is no change in Fiqh without a change in ‘urf.